CORAL RESEARCH IN THE INDONESIAN ARCHIPELAGO, THE PAST, THE PRESENT, AND THE FUTURE - Wijsman-Best, Maya (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1977)
In the past, several big expeditions crossed the Indonesian waters. Coral reefs and their amazing structures and inhabitants were always amongst their special interest. Geomorphological reef theories concerning the Sunda shelf in the Pleistocene period and the barrier reefs in the archipelago have been formulated during the first forty years of the present century. Two major areas of research are discussed i.e. the Bay of Jakarta with emphasis on structure and history of one of two coral islands, Nyamuk and Sakit, and the Togian area in Celebes. The rich tertiary coral reefs, east of the Pleistocene Sunda shelf around Celebes, are treated at the hand of the studies of the geologist, J.H.F. UMBGROVE. This author came across several coral reef problems which are still of present day interest e.g. the diversity and variability of the coral species as a result of the complex ecosystem. Two examples are mentioned to give a general idea of the questions arising in different coral species. Nowadays these problems are normally approached from the geological, physiological, ecological or taxonomic point of view. Even so, in the future many field descriptions will have to be carried out along with zoogeographical work in the main centres of taxonomy, before the species of major influence on the structure of the coral reefs can even merely'be listed.